Existence theories and exact solutions of nonlinear PDEs dominated by singularities and time noise - Ahmed, Muhammad Ozair; Naeem, Rishi; Tarar, Muhammad Akhtar; Iqbal, Muhammad Sajid; İnç, Mustafa; Afzal, Farkhanda (Vilnius Univ, Inst Mathematics & Informatics, 2023)
The current research deals with the exact solutions of the nonlinear partial differential equations having two important difficulties, that is, the coefficient singularities and the stochastic function (white noise). There are four major contributions to contemporary research. One is the mathematical analysis where the explicit a priori estimates for the existence of solutions are constructed by Schauder's fixed point theorem. Secondly, the control of the solution behavior subject to the singular parameter E when E -> 0. Thirdly, the impact of noise that is present in the differential equation has been successfully handled in exact solutions. The final contribution is to simulate the exact solutions and explain the plots.
Keywords: singular partial differential equations; noise function; exact solutions; Schauder?s fixed point theorem; a priori estimates